ENHANCEMENT OF THE CALISTUNG PROGRAM IN WATANG PANJANG VILLAGE - Emalia Nova Sustyorini; Rivatul Ridho Elvierayani (Jurnal Scientia, 2023)
This study aims to determine the increase in calistung in Watang Panjang Village. This study uses a qualitative research approach design. The main object of this research is the calistung program in Watang Panjang Village. The location of this research is Watang Panjang Village, Karangbinangun District, Lamongan Regency. The data in this study is the calistung program in Watang Panjang Village. Data collection techniques used are observation, interviews, and recording techniques. The technique used is descriptive analysis technique. The results of the calistung research program in Watang Panjang Village are: The results of observations during teaching and learning activities in the classroom and Watang Panjang Village Hall, data found that children who cannot read do not mean they do not know letters at all, but do not yet have the concept of when a letter combined with other letters will form words. There are several methods applied in learning calistung in Watang Panjang Village, namely: Questions and answers, storytelling, and groups.